Frequency of Mutations in Brca1 and Brca2 Genes in Women with Breast Cancer in Córdoba, Argentina - Bella, Santiago Rafael (2015)
The discovery of BRCA1 and BRCA2 genes has led to the introduction of increasingly sophisticated genetic tests to measure the risk of hereditary breast cancer, among other things. The aim of this study was to determine the prevalence of the mutation in 24 women from Córdoba with breast / ovarian cancer (BC / OC) and with at least two relatives with breast cancer. Although there are recurrent mutations, which appear repeatedly in unrelated families, with highest prevalence as in the Jewish ethnicity, this is the first study on the population of the province of Córdoba, Argentina.